2012
DOI: 10.1098/rspb.2012.0440
|View full text |Cite
|
Sign up to set email alerts
|

A broader model for C 4 photosynthesis evolution in plants inferred from the goosefoot family (Chenopodiaceae s.s.)

Abstract: C 4 photosynthesis is a fascinating example of parallel evolution of a complex trait involving multiple genetic, biochemical and anatomical changes. It is seen as an adaptation to deleteriously high levels of photorespiration. The current scenario for C 4 evolution inferred from grasses is that it originated subsequent to the Oligocene decline in CO 2 levels, is promoted in open habitats, acts as a pre-adaptation to drought resistance, and, once gained, is not subsequently lost. We test the generality of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
96
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 57 publications
(114 reference statements)
7
96
0
1
Order By: Relevance
“…The classic example is asexuality which arises often but is rarely shared by all members of large, deep clades, leading to suggestions that asexual species lack the genetic variation needed for long-term evolutionary persistence [21]. It has also been suggested that lineages in saline environments may have increased extinction rates [19]. Third, a highly labile trait could show a tippy pattern if it is often gained and lost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The classic example is asexuality which arises often but is rarely shared by all members of large, deep clades, leading to suggestions that asexual species lack the genetic variation needed for long-term evolutionary persistence [21]. It has also been suggested that lineages in saline environments may have increased extinction rates [19]. Third, a highly labile trait could show a tippy pattern if it is often gained and lost.…”
Section: Discussionmentioning
confidence: 99%
“…Chenopodacieae; [19]), most origins of salt-tolerance in grasses are close to the tips of the phylogeny. Most major groups of grasses contain some halophyte species, typically arising from a relatively large number of origins rather than clustering together (see the electronic supplementary material, figure S3), so that most salt-tolerant species have few close halophytic relatives.…”
Section: Discussionmentioning
confidence: 99%
“…This is also demonstrated by the occurrence of pEV as a moderately repetitive and highly diverged repeat in C. quinoa . Because the split of the Betoideae and Chenopodioideae was estimated 52.7 MYA [Kadereit et al, 2012], we speculate that the pEV satellite might be older than 50-60 million years, characterizing pEV as an ancient satellite family that occurs in species of Betoideae and Chenopodioideae. In Anemone blanda , the age of a satellite DNA family was estimated to be 27 million years [Hagemann et al, 1993] suggesting that satellite families in plant genomes are already present for millions of years.…”
Section: Discussionmentioning
confidence: 99%
“…have long been considered two closely related families of the order Caryophyllales and they were subject to taxonomical revisions from the time they were first described to the present (Iamonico 2008(Iamonico , 2012(Iamonico , 2014Kadereit & al. 2003Kadereit & al. , 2012.…”
Section: Introductionmentioning
confidence: 99%